One or Many Recoveries? Recoveries in the Plural for a Better Understanding of One's Healing Journey - Elena Faccio; Michele Rocelli; Lia Bitetti; Giuseppe Salamina; Susanna Brunelli; Federica Mangione; Ludovica Aquili (Health Expectations)
ABSTRACT Background Since the 60s, the recovery‐oriented approach has greatly influenced mental health policy and practice, and much research has been devoted to exploring it. In the face of a generic definition of the ‘recovery’ construct, to which many articles refer, a closer examination of the literature reveals a plurality of theories and ways about how changes related to the recovery occur and how to evaluate them. Aims This narrative review explores the different definitions of recovery available in the literature, by investigating the adjectives that qualify it and the theoretical construct the adjective refers to. Method From the online databases PubMed, Scopus, Google Scholar and PsycINFO, 43 articles were selected for the review. Results Seven definitions of recovery emerged, each supported by specific theoretical perspectives: clinical, personal, narrative, social, family, cultural and relational recovery. The adjectives refer to theoretical frameworks often very distant from each other and in epistemological competition; nevertheless, many papers assume a reconcilability and possible integration. The authors critically discuss the advantages and risks of considering such different constructs as complementary. Conclusions Keeping theoretical descriptions and models of healing open and plural means enabling mental health practitioners not to monologise discourses of change by imposing their point of view on users. It means supporting users to authentically seek their healing pathways without conforming to clinicians' expectations. It also means abandoning misleading and naive simplifications and strictly using the appropriate terms relevant to the specific healing construct that researchers refer to from time to time. This is particularly important when it comes to the relational component, which seems to be receiving more and more attention in the literature, and about which there is more confusion. Patient or Public Involvement The study involved two experts by experience, or peer support specialists, in a more than active role as components of the research team. They participated equally with the other team members in all phases of the work: the design and conduct of the study, the discussion of findings and advice about implications and dissemination.